Status gizi pada pasien penyakit ginjal kronik stadium 5 yang menjalani hemodialisis adekuat dan tidak adekuat - Lajuck, Karsa S.; Moeis, Emma B.; Wongkar, Maarthen C.P. (e-CliniC, 2016)
Abstract: In stage 5 of chronic kidney disease, there is a progressive and irreversible damage in the kidney, therefore, the body is unable to maintain the normal metabolism as well as the fluid and electrolyte balance resulting in the increase of ureum. The management of patients in this stage is hemodialysis, a kind of kidney replacement therapies. Adequacy of hemodialysis is the determining indicator of dose sufficiency inpatients undergoing hemodialysis. Patients undergoing hemodialysis are under the risk of protein and energy malnutrition caused by the lack of food intake. This condition can be detected by using body mass index (BMI), protein, and albumin. This study was aimed to obtain the difference of nutritional status by measuring the BMI, protein, and albumin level in stage 5 CKD patients based on Kt/v, one of the parameter of dialysis adequacy. The study used a cross sectional design with 32 respondents who fulfilled the inclusion criteria. Data of dialysis adequacy based on Kt/v and nutritional status using BMI, protein, and albumin levels were collected. The results showed that there were 20 respondents with adequate hemodialysis and 12 respondents with inadequate hemodialysis. Respondents aged 20-39 years had more adequate dialysis compared to those aged 40-60 years. The paired sample T-test showed that there was no significant difference between hemodialysis adequacy and BMI (p=0.414). However, there was a significant difference between hemodialysis adequacy and protein (p=0.043) as well as between hemodialysis adequacy and serum albumin (p=0.032). Conclusion: Nutritional status (protein and albumin) is a risk factor in stage 5 CKD patients with inadequate and adequate hemodialysis.Keywords: patients with stage 5 chronic kidney disease on hemodialysis, nutritional status, adequacy of hemodialysisÂ Abstrak: Pada penyakit ginjal kronik (PGK) stadium 5, ginjal mengalami kerusakan yang progresif dan tidak dapat pulih kembali, tubuh tidak mampu memelihara metabolisme dan gagal memelihara keseimbangan cairan dan elektrolit berakibat peningkatan kadar serum ureum. Penatalaksanaan pasien PGK pada stadium ini yaitu hemodialisis sebagai salah satu tindakan terapi pengganti ginjal (TPG). Adekuasi hemodialisis merupakan indikator penentuan kecukupan dosis hemodialisis. Tindakan hemodialisis berisiko mengalami malnutrisi energi-protein akibat asupan makan yang kurang, juga disebabkan hilangnya protein serum saat tindakan hemodialisis yang dapat dideteksi dengan pengukuran indeks massa tubuh (IMT), protein, dan albumin. Penelitian ini bertujuan untuk mengetahui perbedaan status gizi dengan mengukur IMT, protein, dan albumin pada pasien PGK 5-HD berdasarkan Kt/V, sebagai salah satu parameter adekuasi dialisis. Desain penelitian potong lintang dengan 32 responden yang memenuhi kriteria inklusi. Dilakukan pengumpulan data mengenai adekuasi hemodialisis berdasarkan Kt/V, status gizi menggunakan IMT, protein, dan albumin. Dari hasil penelitian didapatkan 20 responden dengan hemodialisis yang adekuat dan 12 responden dengan hemodialisis yang tidak adekuat, dan kelompok usia 20-39 tahun memiliki hemodialisis yang adekuat dibanding kelompok usia 40-60 tahun. Uji paired sample T-Test mendapatkan tidak ada perbedaan bermakna antara adekuasi hemodialisis dan IMT (p=0,414) tetapi terdapat perbedaan bermakna antara adekuasi hemodialisis dan kadar protein (p=0,043) serta antara adekuasi hemodialisis dan albumin serum (p=0,032). Simpulan: Status gizi (albumin dan protein) merupakan faktor risiko pada pasien PGK 5-HD adekuat dan tidak adekuat. Kata kunci: PGK stadium 5 hemodialisis, status gizi, adekuasi hemodialisis